Effectiveness of the Implementation of the BGN Free Nutritious Meal (MBG) Program on the Nutritional Status of Junior High School Students in Makassar, Indonesia - Alam, Syamsul; Nurfatmi, Rezki (Universitas Islam Negeri Alauddin Makassar, 2025)
Adolescent nutrition is a key determinant of health and human capital, yet in Indonesia, unbalanced diets and inadequate food quality continue to contribute to undernutrition among adolescents. This study aimed to assess the nutritional status and dietary intake of junior high school students participating in a free nutritious meal program implemented through the Satuan Pelayanan Pemenuhan Gizi (SPPG) by the National Nutrition Agency (Badan Gizi Nasional, BGN). A descriptive quantitative study was conducted at SMP Negeri 23 Makassar on May 7, 2025, involving 50 purposively selected students. Data collection included anthropometric measurements—body weight, height, and mid-upper arm circumference (MUAC)—and dietary assessment using a Food Frequency Questionnaire (FFQ). BMI-for-age was classified according to WHO standards. Data analysis applied Chi-square and simple linear regression to examine the association between dietary intake and BMI. Results showed that 38% of students were underweight, 48% had normal nutritional status, and the remainder were overweight or obese. Sex significantly affected BMI (p = 0.020), with females having higher mean BMI than males, while dietary intake category showed no significant association (R² = 0.006; p = 0.588). The SPPG program improved dietary patterns but requires integration with sustained nutrition education, active parental involvement, and regular monitoring to ensure long-term impact.